THE EFFECT OF FINANCIAL LITERACY, EDUCATION LEVEL ON INVESTMENT DECISIONS IN GENERATION Z SMEs - Fitriaty, Fitriaty (Jurnal Mebis, 2023)
This study aims to examine the effect of financial literacy, level of education on the investment decisions of generation Z SMEs, and the mediating effect of financial literacy on the relationship between educational level and investment decisions of Gen Z. The data in this study were obtained by distributing questionnaires to Generation Z in Jambi city using purposive sampling. The data is processed using the Smart-PLS software to test the model and hypothesis. This study found that financial literacy and level of education can influence investment decisions in Generation Z MSME actors. Financial literacy can mediate education level variables and investment decisions in Generation Z MSME actors